Short-term vasoactive agent treatment driven by physicians’ preference in acute esophageal variceal bleeding in a tertiary center - Chuah, Yoen Young; Hsu, Ping-I; Tsai, Wei-Lun; Yu, Hsien-Chung; Tsay, Feng-Woei; Chen, Wen-Chi; Lin, Kung Hung; Lee, Yeong Yeh; Wang, Huay-Min (PeerJ, 2019)
Background Vasoactive drugs are frequently used in combination with endoscopic variceal ligation (EVL) in treatment of acute esophageal variceal bleeding (EVB). The aim of study was to assess physicians’ preference of vasoactive agents in acute EVB, their reasons of preference and efficacy and safety of these short course regimens. Methods Cirrhotic patients with suspected EVB were screened (n = 352). Eligible patients were assigned based on the physician’s preference to either somatostatin (group S) or terlipressin (group T) followed by EVL. In group S, intravenous bolus (250 µg) of somatostatin followed by 250 µg/hour was continued for three days. In group T, 2 mg bolus injection of terlipressin was followed by 1 mg infusion every 6 h for three days. Results A total of 150 patients were enrolled; 41 in group S and 109 in group T. Reasons for physician preference was convenience in administration (77.1%) for group T and good safety profile (73.2%) for group S. Very early rebleeding within 49–120 h occurred in one patient in groups S and T (p = 0.469). Four patients in group S and 14 patients in group T have variceal rebleeding episodes within 6–42 d (p = 0.781). Overall treatment-related adverse effects were compatible in groups S and T (p = 0.878), but the total cost of terlipressin and somatostatin differed i.e., USD 621.32 and USD 496.43 respectively. Conclusions Terlipressin is the preferred vasoactive agent by physicians in our institution for acute EVB. Convenience in administration and safety profile are main considerations of physicians. Safety and hemostatic effects did not differ significantly between short-course somatostatin or terlipressin, although terlipressin is more expensive.
Keywords: Terlipressin; Somatostatin; Esophageal variceal bleeding; Physician preference